Lévinas e il metodo fenomenologico - Carbone, Guelfo (B@belonline, 2020)
Drawing on a particular implementation of the phenomenological method, Lévinas’s ethics challenges both the Husserlian transcendental egology and Heidegger’s fundamental ontology, aiming at a radical critique of the very basic assumptions of Western philosophical and scientific thinking. The paper sketches out the context in which, by assuming the phenomenological method in order to overcome phenomenology itself, Lévinas continues the radicalization of the Cartesian method initiated by Husserl, delving into a path already outlined by Heidegger.